Bloqueio neuromuscular pela capreomicina - Fortes, Virgílio Augusto; Mendes, Reinaldo Poncio; Mendes, Armando Octávio; Bastos, Wilma Pereira (Acta Biológica Paranaense, 1975)
Bloqueio neuromuscular pela capreomicina